Accidental Injection of Chlorhexidine during Endodontic Therapy - Beltran, Hair Salas; Macedo-Serrano, Nathaly; Baldarrago , Andres Castrejon; Iuga, Maria Mihaela; Laura , Leydi Paricahua (Iranian Endodontic Journal, 2021)
The use of chlorhexidine gluconate (CHX) as an irrigating solution in an anesthesia cartridge is a wrong procedure commonly performed in daily clinical practice. Being an invasive procedure, it is invariably associated with complications. A 47-year-old healthy woman was injected accidentally with 2% CHX in the buccal vestibular area instead of an anesthetic solution during a root canal treatment. After the injection, the patient experienced local side effects, such as a burning sensation on the right cheek area, also a discomfort perception at the injection site and a slight inflammation with a mild extraoral redness especially on the right side cheek. The patient was prescribed with antibiotics and anti-inflammatories to reduce pain and inflammation. The patient complained of upper lip numbness by the second day of the accident. The extraoral swelling reduced gradually and the redness diminished considerably over a period of 6 days. At day 60 of follow-up, the patient recovered satisfactorily from extraoral inflammation but still presented a slight numbness of the upper lip. As a conclusion, we can claim that anesthesia cartridges with irrigant solutions should never be used to irrigate the root canals, and accidental injection of CHX should be carefully assessed by the clinician.